High-intensity interval training to promote cerebral oxygenation and affective valence during exercise in individuals with obesity. Issue 13 (3rd July 2022) - Marillier, Mathieu; Borowik, Anna; Chacaroun, Samarmar; Baillieul, Sébastien; Doutreleau, Stéphane; Guinot, Michel; Wuyam, Bernard; Tamisier, Renaud; Pépin, Jean-Louis; Estève, François; Vergès, Samuel; Tessier, Damien; et al.
ABSTRACT: Left/right prefrontal cortex (PFC) activation is linked to positive/negative affects, respectively. Besides, larger left PFC oxygenation during exercise relates to higher cardiorespiratory fitness (CRF). High-intensity interval training (HIIT) is superior to moderate-intensity continuous training (MICT) in improving CRF. The influence of training on PFC oxygenation and affects during exercise in individuals with obesity is, however, currently unknown. Twenty participants with obesity (14 males, 48 ± 8 years, body-mass index = 35 ± 6 kg·m −2 ) were randomised to MICT [50% peak work rate (WRpeak )] or HIIT (1-min bouts 100% WRpeak ; 3 sessions/week, 8 weeks). Before/after training, participants completed an incremental ergocycle test. Near-infrared spectroscopy and the Feeling Scale assessed PFC oxygenation and affects during exercise, respectively. Improvements in CRF (e.g., WRpeak : 32 ± 14 vs 20 ± 13 W) were greater after HIIT vs MICT ( p < 0.05). Only HIIT induced larger left PFC oxygenation (haemoglobin difference from 7 ± 6 to 10 ± 7 μmol) and enhanced affective valence (from 0.7 ± 2.9 to 2.2 ± 2.0; p < 0.05) at intensities ≥ second ventilatory threshold. Exercise-training induced changes in left PFC oxygenation correlated with changes in CRF [e.g., WRpeak (% predicted), r = 0.46] and post-training affective valence (r = 0.45; p < 0.05). HIIT specifically improved left PFC oxygenation and affects during exercise in individuals with obesity. Implementing HIIT in exercise programmes may therefore have relevant implications for the management of obesity, since greater affective response to exercise is thought to be associated with future commitment to physical activity.